Chromosomal Translocation t (10;19) (q11.2;q13.4) in an Infertile Male - Kara, Murat; Sen, Askin; Cetin, Esin Sakalli; Kargun, Kursat (Aves, 2014)
Chromosomal rearrangements are usually associated with male factor infertility. We report here a 34-year-old man suffering from primary infertility for 15 years. The cytogenetic analysis and investigation of Y-chromosome microdeletions were performed. A reciprocal balanced translocation t (10; 19) (q11.2;q13.4) was found in oligozoo-spermic infertile men with no Y-chromosome microdeletions. In this case, we aimed to evaluate the 46,XY, t (10;19) (q11.2;q13.4) karyotype, which was detected through a cytogenetic analysis of a person referred to our genetic laboratory due to primary infertility, in the light of the literature.
İnfertil bir erkekte t (10;19) (q11.2;q13.4) kromozomal translokasyonu
Keywords: Chromosomal translocation; infertility